Training and Development in the Private Sector: An Empirical Study of Alliance One Tobacco Tanzania Limited in Morogoro Municipality - Kumar, Varikallu Harish (Journal of Global Economy, Business and Finance, 2025)
The purpose of this study was to examine the extent to which training and development programs are being implemented in private sector organizations, a case study of Alliance One Tobacco Tanzania Limited (AOTTL). The target population of this study was 207 respondents. A sample size of 88 respondents that include 13 top and middle management personnel and 75 laborers was used. Purposive sampling techniques and convenience sampling techniques were used in selection of respondents. Data were collected by using questionnaire, interviews and documentary reviews. Quantitative data were analyzed by using descriptive statistics while qualitative data were analyzed by using content analysis. The study found that, training and development programs align with the needs of the organizations, training and development program objectives are clearly defined, sufficient resources are not allocated to support the implementation of training and development programs, training and development programs are not always effectively communicated to employees in organizations, and training and development programs are not regularly evaluated. The study recommends that, it is essential to allocate adequate resources, including budget, time, and personnel, to support the implementation of training and development programs. Furthermore, effective communication is crucial to ensure that employees are aware of and understand the training and development programs available to them.